Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Disrupted white matter functional connectivity in aMCI APOEε4 carriers: a resting-state study - Hua Lin; Muwei Li; Yang Zhan; Li Lin; Kun Yang; Shimin Hu; Ying Han (Brain Imaging and Behavior, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)